Magnetic resonance imaging of the brain in patients with cerebral malaria. - Looareesuwan, S; Wilairatana, P; Krishna, S; Kendall, B; Vannaphan, S; Viravan, C; White, N (1995)
In a prospective study of cerebral malaria, 24 adults with this disease underwent magnetic resonance imaging (MRI) of the brain. Four patients died. Two of these patients (nos. 17 and 24) had breathing abnormalities requiring ventilatory support followed by clinical signs of brain death. Four days later MRI of patient 17 showed gross swelling of the brain, and 5 hours later MRI of patient 24 showed foramen magnum herniation. Twenty-two patients had no evidence of cerebral edema, but MRI revealed that brain volume during acute cerebral malaria was slightly greater than that during the convalescent phase of the disease. This difference was attributed to an increase in the volume of intracerebral blood. The cerebral volume was lower during early convalescence than several months later. The volume of the brain in patients with cerebral malaria is increased. This increased volume probably results from sequestration of parasitized erythrocytes and compensatory vasodilatation rather than from edema. Brain stem herniation may occur, but its temporal relation to brain death in cases of cerebral malaria remains uncertain.